Sosialisasi Dan Pelatihan Pembuatan Sabun Alami Berbasis Limbah Clay Dari Industri Gerabah Dengan Mitra Koperasi Syariah Lingkar (KSL) Rinjani Lombok - Hamdiani, Saprini; Kamali, Siti Raudhatul; Hadisaputra, Saprizal; Indriyatno, Indriyatno; Arisanti, Ivon (Universitas Mataram, 2025)
This community development program was motivated by the large amount of broken pottery waste generated during the firing process that remains unutilized in the traditional pottery industry of Banyumulek Village. The clay waste has significant potential as an innovative additive in the production of natural soap. The purpose of this activity was to enhance community awareness and skills, particularly among members of KSL Rinjani Lombok, in processing waste into environmentally friendly and economically valuable products. The implementation methods included socialization and training. The socialization stage provided understanding of the potential of clay waste and opportunities for developing natural soap products, while the training stage was conducted through hands-on practice covering material preparation, mixing with soap base ingredients, and soap molding techniques. The results of the activity showed an increase in participants’ knowledge and skills in utilizing clay waste, with the highest improvement reaching 85%. Community partners were able to produce natural soap with good quality and market potential. In addition, the program successfully achieved its objectives by empowering the community through innovative utilization of pottery waste, while fostering the creation of competitive and eco-friendly product.